(untitled) (International Journal of Engineering and Computer Science, 2017)
The Diffie-Hellman key exchange protocol provides the opportunity to arrive at a common secret key by exchanging texts over insecure medium without meeting in advance. Diffie-Hellman key exchange protocol is limited to the exchange of key only. Due to lack of authentication of entities, this protocol is vulnerable towards man-in-middle attack and impersonation attack. To eliminate the man-in-middle attack, Nanli[9] presented a research paper on Diffie-Hellma key exchange protocol. It is observed that Nanli‟s protocol, still suffers with impersonation attack. To deal with this vulnerability, an improved key exchange approach based on third party authentication scheme is proposed in this paper.